1994
DOI: 10.1089/ard.1994.4.291
|View full text |Cite
|
Sign up to set email alerts
|

Iontophoretic Delivery of Oligonucleotide Derivatives into Mouse Tumor

Abstract: Oligodeoxyribonucleotides (22-mers) were delivered through the skin of C3H mice in the region of a mammary gland tumor by means of iontophoresis. It was shown that the oligonucleotides enter the tumor, cross it, and reach all mouse organs. Electrophoretic analysis of the oligonucleotide extracted from tumor showed that the compounds were delivered in the tissue in the intact state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…To control for sample loading, the membrane was reprobed with a monoclonal antibody against a-tubulin. uptake mechanisms and intracellular trafficking of PS-ODN in cell lines [29,30]. Therefore, we investigated the mechanisms which are involved in cellular uptake and trafficking of the PS-ODN-P in the presence and absence of LF in CD8 þ T cells.…”
Section: Involvement Of Different Mechanisms In the Uptake Of Ps-odnsmentioning
confidence: 99%
“…To control for sample loading, the membrane was reprobed with a monoclonal antibody against a-tubulin. uptake mechanisms and intracellular trafficking of PS-ODN in cell lines [29,30]. Therefore, we investigated the mechanisms which are involved in cellular uptake and trafficking of the PS-ODN-P in the presence and absence of LF in CD8 þ T cells.…”
Section: Involvement Of Different Mechanisms In the Uptake Of Ps-odnsmentioning
confidence: 99%
“…Penetration using physical enhancement techniques, such as iontophoresis (Brand and Iversen, 1996) and electroporation (Regnier et al, 1998), have been used to deliver PS-ODN successfully in vitro. Vlassov et al (1993Vlassov et al ( , 1994 demonstrated measurable tissue levels in mice of oligonucleotides after iontophoresis in vivo. However, functional evidence is lacking as to the effectiveness of these compounds when given transdermally.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies have shown that antisense oligomers can enter into target organs (Vlassov et al, 1993;Vlassov et al, 1994), and induce changes in target enzymes (Brand et al, 2001;Arora et al, 2002). The transdermal delivery of neutral PMOs using chemical penetration enhancement techniques has yet to be investigated, though preliminary data has demonstrated that the flux of a PMO targeted to cytochrome P4503A2 in propylene glycol and linoleic acid was nearly 20 times greater than that reported with iontophoretic delivery of the same sequence with a phosphorothioate (PS) backbone (Brand and Iversen, 2000).…”
Section: Introductionmentioning
confidence: 99%